The Role Of International Non-Governmental Organizations (NGOs) In Disaster Management Of Mt. Sinabung Eruption In Karo District, North Sumatra, Indonesia - Tiffany Setyo Pratiwi; Syafira Fajri Br Sitepu (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
This study aims to determine the role of Non-Governmental Organizations (NGOs) in managing the eruption of Mount Sinabung. The eruption of Mount Sinabung in 2010 and another eruption in 2013 had a major impact on the people living around Mount Sinabung. The role of various parties was carried out, including the presence of an international Non-Governmental Organization (NGO) in Karo Regency. This paper will describe the role of NGOs using the concept of disaster management which consists of pre-disaster, emergency response, and post-disaster stages. In this study, it was found that during the pre-disaster stage the international NGOs present were FM Yoboseyo Yumen (FMYY) Japan and Mercy Malaysia. During the emergency response stage, the World Food Program (WFP) was present in Karo District. At the post-disaster stage are the United Nations Development Program (UNDP), the International Labor Organization (ILO), and the Food and Agriculture Organization (FAO). This research method used a qualitative approach with descriptive research types, and data collection through interviews and secondary data.